THE ACTION OF COLEUS AROMATICUS AS A POTENTIAL WOUND HEALING AGENT IN EXPERIMENTALLY INDUCED DIABETIC MICE - Kalesware Muniandy; Zaiton Hassan; Mohd Hafez Mohd Isa (PERINTIS eJournal, 2021)
The ethanolic and aqueous extract of Coleus aromaticus leaves and roots were evaluated for its wound healing activity in diabetic mice induced experimentally with Monosodium Glutamate (MSG) via excision and dead space wound models with the application of 100 mg kg-1 of body weight of extract. Excision wound was created on five different groups of mice and the wound contraction was measured for ten uninterrupted days. Dead space wound model was performed on four different groups of mice for the estimation of the weight of both wet and dry granulation tissue followed by the histological investigation of the wet granulation tissue after ten days. Ethanolic extract treated wounds showed 76.6% of wound area reduction compared to the controls that only showed 55.9 % of wound area reduction. The rate of epithelialization in ethanolic extract treated mice was interestingly higher compared to the controls. Histological investigation shows an increase in granulation tissue, good proliferation of collagen tissue and satisfactory angiogenesis in the leaves and root extract treated mice compared to the controls. Coleus aromaticus stimulates significant wound healing in experimentally induced diabetic mice and evaluation of the effectiveness of Coleus aromaticus as wound healing agent on human organism is highly suggested.